Epithelioid hemangioma of the ascending aorta: A rare case - Ivan S Murashov; Yuliya E Kareva; Evgenii E Kliver; Aleksandr Volkov (Wolters Kluwer Medknow Publications, 2022)
Cardiac epithelioid hemangioma is extremely rare. Currently, there are only a few described cases of intraluminal hemangiomas of the aorta and the aortic valve and no described cases with extraluminal epithelioid hemangiomas of the ascending aorta. We now present a case of epithelioid hemangioma of the ascending aorta that was an incidental finding during the coronary artery bypass and successfully resected.